Customer Perception of Mobile Banking - A Case Study - Namarta Arora (International Journal on Economics, Finance and Sustainable Development, 2022)
Technology has turned into an inevitable part of all industries across the globe. This is especially true in the case of banking industry, where the technology plays an important role in fostering the banking sector. Currently banks have adopted wireless services and mobile technology in their operations to provide their customers with upgraded services; from bill payments through mobile phones to receiving marketing updates while they are stuck in a traffic jam. Mobile Banking services provide more personal and near relationships. This paper examines consumer satisfaction of a new electronic payment of service as mobile banking and the factors influencing the adoption of mobile banking services. The advent of internet has great contact on the electronic banking. By using internet, banking is no time limit and geographic. This type of banking is partially web-based banking subsidiary with the difference is that web banking services. Commercial bank was considered first introduced bank and service. Internet banking also extended with the development of web applications. This study focus on the customers’ perception towards mobile banking services in Panipat district. It gives the useful suggestions based on the findings to the banks. There are primary and secondary data used for this study. Interview schedule is used for collecting primary data. The primary data was analysed with the various statistical tools. This study gives the useful suggestions to the customers. Finally this study concluded that the maximum customers strongly agreed the various mobile banking services.